OPTIMALISASI STRATEGI THINK TALKWRITE (TTW) UNTUK MENINGKATKAN KEMAMPUAN MENULIS KARANGANTEKS DESKRIPTIF SISWA DI SDN 1 MANIKYANG - I Nyoman Sudiana; I Gusti Agung Ayu Lily Purnami; Ni Luh Nyoman Wina Wahini; Yuni Nuryanti; Putri Hidayah; Gusti Ngurah Bagus Tirtayadna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the Think Talk Write (TTW) learning model in improving the descriptive text writing skills of fourth-grade students at SDN 1 Manikyang. The TTW model is implemented as a learning strategy that encourages students to think critically, engage in discussions, and express their ideas in a more structured written form. The research method used is quantitative with an experimental approach, employing a pre-test and post-test design, where data is collected through an assessment of students' writing performance before and after the implementation of the TTW model. The results of the study indicate a significant improvement in students' writing abilities after the application of the TTW model. The average student score increased from 67.94 in the pre-test to 75.00 in the post-test. Before the implementation of the TTW model, the majority of students were in the fair category (58.82%) and poor category (35.29%). However, after the intervention, most students fell into the good category (58.8%) and very good category (20.6%). Furthermore, no students remained in the poor or very poor categories after the implementation.